Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/1461318
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Fiber Bridging Model for High Ductility Cementitious Composites Based on Debonding-Slipping Rupture Analysis

Abstract: Modified micromechanical bridging model is established with consideration of the fiber rupture effect at debonding and slipping stages. The bridging model includes the debonding and slipping rupture of fibers and establishes the fiber/matrix interfacial parameters (friction τ 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…To improve the mechanical properties of HDCC, especially its compressive strength, some researchers have tried to optimize the HDCC by finding the optimal fiber length. Ding [11] studied the effects of fiber length on the mechanical properties of HDCC with PVA fibers 6, 9, 12, 18, and 24 mm in length. The results showed that the optimum length of the PVA fibers was 9 mm, and the compressive strength of the HDCC increased by 15%.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the mechanical properties of HDCC, especially its compressive strength, some researchers have tried to optimize the HDCC by finding the optimal fiber length. Ding [11] studied the effects of fiber length on the mechanical properties of HDCC with PVA fibers 6, 9, 12, 18, and 24 mm in length. The results showed that the optimum length of the PVA fibers was 9 mm, and the compressive strength of the HDCC increased by 15%.…”
Section: Introductionmentioning
confidence: 99%